METODOLOGI PENELITIAN SURVEI UNTUK PENELITIAN MANAJEMEN PENDIDIKAN ISLAM - M. Fahmi Rofiudlofir. AK; Moch. Varhana Yafrizal; Irawan Irawan (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2022)
This research aims to elucidate the quantitative scientific research method using a survey approach in the field of Islamic educational management. This research method employs library research and descriptive analysis to comprehend the collected data. The results indicate that the survey approach is an effective method for portraying population aspects by gathering information through interviews or questionnaires. Questionnaires are employed as the primary tool in data collection, characterized by scientific traits such as determinism, parsimony, generality, logic, and specificity. This method is suitable for depicting phenomena and analyzing issues within the management of Islamic educational institutions. The research steps encompass problem identification, hypothesis formulation, objective establishment, selection of survey type, sample design, determination of sample size, construction of questions and assessment tools, data collection in line with conceptual definitions, data processing and analysis, evaluation of analysis outcomes, and report compilation.